An Analysis Of Solar Power Plan Optimization With Solar Reflector Angle Variation Based On IOT - Selamat Riady Hutasuhut; Solly Aryza; Beni Satria (INFOKUM, 2025)
This study analyzes the optimization of solar power generation by varying the angle of solar reflectors based on the internet of things (iot). The research aims to determine the most effective reflector angle to maximize the efficiency of solar energy absorption in solar power plants. By utilizing iot technology, real-time monitoring and adjustment of the reflector angles can be achieved to enhance energy capture throughout the day. The methodology involves both experimental and simulation approaches to compare different angles under various environmental conditions. The results of the study indicate that optimal reflector angles significantly improve the overall efficiency of solar power generation. This research contributes to the development of more efficient and sustainable solar power systems by leveraging iot for precise and responsive control mechanisms.